Intrapatient tacrolimus variability is associated with medical nonadherence among pediatric kidney transplant recipients - Gavcovich, Tara B.; Sigurjonsdottir, Vaka K.; DeFreitas, Marissa J.; Serrano, Claudia; Rivas, Esther; Jorge, Migdalia; Seeherunvong, Wacharee; Katsoufis, Chryso; Glaberson, Wendy; Oliva, Melisa; Mattiazzi, Adela D.; Abitbol, Carolyn; et al. (Frontiers in Transplantation, 2025)
BackgroundLong-term survival of kidney allografts is limited by multiple factors, including nonadherence. High intrapatient variability in tacrolimus levels (≥30%) is associated with de novo donor-specific antibody (dnDSA) formation, increased risk of rejection and graft loss.MethodsWe prospectively analyzed the association between tacrolimus intrapatient variability and nonadherence in pediatric kidney transplant recipients. We derived a composite adherence score from 0 to 3 points based on (1) Basel Assessment of Adherence to Immunosuppressive Medical Scale©; (2) healthcare team score; and (3) intentionally missed laboratory or clinic visits. A score of 1 or more was considered nonadherent. Tacrolimus 12 h trough levels, patient characteristics and clinical outcomes were collected. Tacrolimus IPV was calculated as the coefficient of variation.ResultsThe nonadherent group had a significantly higher median tacrolimus intrapatient variability (31%) as compared to the adherent cohort (20%) (p < 0.001.) Tac IPV demonstrated strong predictive performance for adherence (AUC 0.772), with a particularly high sensitivity of 90% at thresholds up to 20%, offering a practical and actionable framework for assessing adherence-related risks in clinical practice.ConclusionsTacrolimus intrapatient variability may be a useful biomarker to identify nonadherence and high-risk patients, allowing for early interventions to prevent adverse graft outcomes.